Malignant Adenomyoepithelioma of the Breast with Lymph Node Metastasis: A Detailed Immunohistochemical Study - Ahlam A. Awamleh; Mihir Gudi; Sami Shousha (Case Reports in Pathology)
Malignant adenomyoepithelioma of the breast is a rare tumour with around 30 cases reported in the literature. Metastases associated with these tumours are usually haematogenous. Axillary lymph node metastases are thought to be unusual, and it has been recently suggested that axillary node dissection is not indicated unless clinically palpable. We here present a case of a 63-year-old woman, who developed a malignant adenomyoepithelioma with axillary lymph node metastasis, that included epithelial and myoepithelial elements, in spite of the absence of clinically enlarged nodes. We suggest that histological examination of axillary sentinel node(s) or node sampling may be worthwhile in this condition.